Enhancing justice through effective utilisation of ‘Dispute Resolution Mechanisms’ in handling medical disputes in Indonesia - Susila, Muh Endriyo; Jahn Kassim, Puteri Nemie (International Islamic University Malaysia, 2017)
Medical disputes amongst medical professionals and their patients are seen to be inevitable, particularly, when patients suffer adverse outcome in medical treatment. The occurrences of death and physical injuries tend to trigger claims in the court of law. Consequently, medical professionals may be subjected to criminal proceedings although their actions in causing the harm may be totally unintentional. The implications of court litigation against medical professionals may adversely affect the reputation of doctors in the long run and this will eventually promote the practice of defensive medicine. Therefore, it is pertinent that court litigation for resolving medical disputes should be taken only as a last resort after fully utilising the existing ‘dispute resolution mechanisms’ that are available. Presently, there are a variety of ‘dispute resolution mechanisms’ available in Indonesia to solve medical disputes, for instance, through medical as well as consumer tribunals and various methods of alternative dispute resolution. However, to ensure proper utilisation of these mechanisms for solving medical disputes, the role and inadequacies of these mechanisms should be properly addressed to ensure a more effective, fair and just outcome. This paper seeks to identify and discuss the role of existing ‘dispute resolution mechanisms’ in handling medical disputes in Indonesia. The adequacies and inadequacies of these mechanisms will be highlighted and the agendas for reform will also be proposed in order to promote the use of these mechanisms as an alternative to court litigation in resolving medical disputes in a more amicable manner within the modern healthcare setting.